ISOLATION AND CHARACTERIZATION OF COMPOUND FROM THE LEAF EXTRACT OF ALBIZIA CHEVALIERI : LEAF EXTRACT OF ALBIZIA CHEVALIERI - Danjuma, Kabir; Jibrin, Moses; Abdu, Kabir; Lawan, Imrana; Amayindi, Magaji; Tasnim, Tasnim (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Albizia chevalieri is a medicinal plant that grows up to 12 m height under temperate condition of the dry savanna in the republic of Niger, Nigeria, Senegal and Cameroon. This study was performed to isolate and characterize a compound from the leaf extract of Albizia chevalieri. Methods: The crude extract was obtained by macerating the powdered sample of Albizia chevalieri which was further fractionated with n-hexane, dichloromethane, acetone and methanol solvents. The dichloromethane was subjected to column chromatography packed with silica gel for the isolation of compound. The isolated compounds were further purified using Preparative Thin Layer Chromatography which yielded compound. The isolated compound was characterized by subjecting it to Fourier Transform Infrared Resonance Spectroscopy (FTIR), and Proton and Carbon-13 Nuclear Magnetic resonance spectroscopy (proton and carbon-13 NMR) techniques Results: From the results, it has been observed that acetone extract has the highest percentage yield (50.15 %), followed by n-hexane extract (25 %), dichloromethane extract (16.87 %), ethanol extract (12.00 %), and then methanol extract (7.70 %), respectively. FTIR analysis reveals the presence of -OH, -C-H, C=O, and C-O. functional groups. Chromatographic separation revealed a compound obtained at a retention factor of 0.4. The compound isolated was named 3a-Methyl-oxo-1-(3,4,5-trihydroxy-6-hydroxymethyl-tetrahydro-pyran-2-yloxy)-octahydro-indene-5-carboxylic acid using the information provided by the FTIR and NMR, respectively. Conclusion: The result of this research could pave the way for the evaluation of the pharmacological activities of the isolated compound, thereby providing scientific validation for the ethnomedicinal usage of Albizia chevaieri leaf in the treatment of different numerous diseases.